IMPLEMENTASI PENDEKATAN SCIENTIFIC DALAM PENGAJARAN BAHASA INGGRIS KURIKULUM 2013 DI SMPN 1 PAMEKASAN - Siti Azizah; Eko Ariwidodo; Iswah Adriana (IAIN MADURA, 2015)
This article is a summary of a group research describing the implementation of scientific approach in teaching English of Curriculum 2013 at SMPN 1 Pamekasan. Scientific approach is an approach focusing on investigation techniques on phenomena, getting new knowledge, or correcting and relating the previous knowledge. Scientific approach is a new approach in teaching English. This research has three study focuses that is: 1) How the English teachers of the seventh grade plan English learning process by using scientific approach 2) How the implemntation of scientific approach in teaching English of Curriculum 2013 at SMPN 1 Pamekasan 3) What problems or difficulties faced by the English teachers in implementing the scientific approach. The Research result shows the first, English teachers of the seventh grade at SMPN 1 Pamekasan plan their English learning process by writing the lesson plan first. Second, the implementation of scientific approach in teaching English of Curriculum 2013 at SMPN 1 Pamekasan on the first year does not run well. Third, most of English teachers of the seventh grade at SMPN 1 Pamekasan get difficulties in facilitating the students to ask and answer the questions to their friends or teacher. It means that the teachers still get difficulties in questioning step of scientific approach.